Analysis Of Factors Related To Covid-19 Prevention Efforts Among Health Sciences College Students In Cirebon 2022 - Awis Hamid Dani; Dwi Nastiti Iswarawanti; Esty Febriyani; Dewi Laelatul Badriyah (Eduvest - Journal of Universal Studies, 2024)
The negative information bias on social media can lead to a wrong perspective on COVID-19 cases and cause behavior in efforts to prevent COVID-19 to get worse, so that deaths continue to increase and continue to grow. Based on data from 231 countries that have confirmed COVID-19 with a total of 516,476,402 people and 6,258,023 people died, while in Indonesia, 6,049,541 people have recovered, and 5,887,786 have died and 156,424 have died. , while the confirmed cases of COVID-19 in West Java were 1,106,085, the cure rate was 1,089,648 and 15,795 died. The research method used is descriptive analytic research using a cross sectional research design. The subject of this research is STIKes Cirebon students with a population of 1286 students. The sampling technique used is disproportionate stratified random sampling, then takes the appropriate number of samples by simple random sampling to become respondents obtained a sample of 122 respondents, research instruments using questionnaires, data analysis using univariate, bivariate and multivariate analysis. The results showed that the relationship between frequency (p=0.043), duration (p=0.606), attention (p=0.038) and health literacy with COVID-19 prevention efforts (p=0.017). Attention variable is the most dominant variable with p value 0.026, OR value 2.787. There are 3 variables that are related and 1 variable that is not related to efforts to prevent COVID-19, where the most dominant variable is attention.